1997
DOI: 10.1177/096120339700600407
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate use in systemic lupus erythematosus

Abstract: Low dose pulse oral methotrexate (MTX) is a well established treatment for rheumatoid arthritis, and short term open studies have suggested beneficial effects of MTX in SLE. This study was designed to investigate MTX treatment maintenance rates in SLE using life table analysis, and to determine whether MTX use was associated with a dose reduction of concomitant steroid therapy. All SLE patients managed by physicians affiliated with a single centre were studied cross-sectionally. Information regarding disease v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…This systematic literature review yielded 22 studies reporting discontinuation rates due to side effects in patients with SLE taking MMF, MTX, AZA, CYC, or CsA (Table 2) [17, 18, 22–27, 29, 3236, 38, 39, 45, 46, 50, 51, 53, 54]. Overall, these rates were generally similar across treatments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic literature review yielded 22 studies reporting discontinuation rates due to side effects in patients with SLE taking MMF, MTX, AZA, CYC, or CsA (Table 2) [17, 18, 22–27, 29, 3236, 38, 39, 45, 46, 50, 51, 53, 54]. Overall, these rates were generally similar across treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies analyzed AZA, reporting rates from 2.3% to 21.8% across study types [18, 23, 3235, 39, 54]. Only three studies reported discontinuation rates due to AEs in patients taking MTX, with a range of 8.3% to 12.2% [29, 53, 54]. …”
Section: Resultsmentioning
confidence: 99%
“…Methotrexate is a cytotoxic drug of the folate antagonist group, which when used in the context of SLE has beneficial immunosuppressant effects, even when prescribed with folic acid. The effects of methotrexate on cytokine profiles in mouse models of SLE have been documented [18] but there have as yet been relatively few trials of methotrexate in humans [19–22]. It seems to be effective for treatment of skin, joint and muscle manifestations; however, its use in the presence of renal or CNS lupus has not been studied.…”
Section: Treatmentmentioning
confidence: 99%
“…La explicación está en primer lugar, en la falta de respuesta satisfactoria al tratamiento previo, en lo que se refiere a manifestaciones articulares y cutáneas, y muy relacionado con esto, en la necesidad de usar dosis de corticoesteroides no deseables y desproporcionadas a las manifestaciones predominantes en esa etapa evolutiva como eran las señaladas; en segundo lugar, porque durante un largo tiempo el MTX no se consideró una alternativa válida para ser usada en pacientes lúpicos. Sin embargo, y como ya se señaló, la progresiva experiencia internacional ha permitido orientar su uso precisamente en estas manifestaciones y más aún si no ha habido una respuesta satisfactoria a los corticoides, antimaláricos o inmunosupresores [4][5][6][7][8][13][14][15][17][18][19][20][21] .…”
Section: Discussionunclassified